2017
DOI: 10.1039/c7ce00983f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant polysaccharides with different carboxyl group contents on calcium oxalate crystal growth

Abstract: The effects of five plant polysaccharides (PPSs) with molecular weights of ∼4000 Da and different carboxylic group (–COOH) contents on the crystal growth of calcium oxalate (CaOx) were comparatively studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…Crystallization of CaOx. Experiments were carried out with slight modification according to Reference [19]. The reaction was maintained and conducted in a 100 mL beaker at 37°C.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Crystallization of CaOx. Experiments were carried out with slight modification according to Reference [19]. The reaction was maintained and conducted in a 100 mL beaker at 37°C.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Figure 4(a) shows that the diffraction peaks of COD were strengthened as CSP0 concentration increased, suggesting an enhancement in the induced amount of COD. According to the quantitative calculation of K value method [9], in the presence of CSP0 of 0.1, 0.3, 0.4, 0.5, 0.8, and 1.0 mg/mL, the percentage content of COD in the generated CaOx crystal was 0, 8.6%, 32.6%, 61.0%, 82.0%, and 86.5%, respectively (Figure 4(c)). Figure 4(b) and Table 3 show the FT-IR spectra of CaOx crystal as CSP0 concentration increased, υ as (COO-) blue shift continuously.…”
Section: Effect Of Csp0 Concentration On Calcium Oxalate Crystalmentioning
confidence: 99%
“…Gomes et al [8] investigated the antiurolithic ability of sulfated seaweed polysaccharide (SP) and found that SP can change the surface charge of crystal, induce the morphology of CaOx crystal to become round and blunt, and reduce the crystal size. Huang et al [9] explored the effects of five kinds of plant polysaccharides with different carboxyl contents on the growth of CaOx crystals. The results showed that five kinds of plant polysaccharides can inhibit the growth of COM, induce the formation of COD, and reduce the aggregation of crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular weight of TPSs affected their protective effect on HK-2 cells. The cell membrane cannot be crossed when the molecular weights of the TPSs were large (e.g., 10.88 kDa of TPS0) [25,26]. However, the hydrogen chain was weak, and the active helical structure was not formed because of the short sugar chain [27,28] when the molecular weight of TPSs was small (such as 2.31 kDa of TPS3), thereby leading to a decrease in the protective effect.…”
Section: Reduction Of Cytotoxicity Of Com Crystals Aftermentioning
confidence: 99%